Hubungan Presiden dan Dewan Perwakilan Rakyat Pasca Amendemen Perspektif Teori Constitutional Retrogression - Ilham Habiburohman (Jurnal Hukum IUS QUIA IUSTUM, 2021)
The term Constitutional Retrogression was introduced by Aziz Huq and Tom Ginsburg to identify regress of the constitution, given that the constitution is formed as a safeguard for democracy. This identification is based on three basic principles of democracy, namely, competitive elections, freedom of speech and assembly and the quality of the law. In recent years, proposals for government regulations to replace laws submitted by the President have received the blessing of the House of Representatives (DPR). Whereas in substance it is still considered problematic; such as the promulgation of Perppu No. 1 of 2017 on Social Organizations. This study uses a normative juridical method with a statutory and conceptual approach. The results of the study conclude that the relationship between the President and the DPR after the amendment to the 1945 Constitution has indicated Constitutional Retrogression, hence this study proposes several preventive measures, first, amending the regulations on the presidential threshold; second, elections in a multiparty system are held in a proportional system with an open list approach; third, the Constitutional Court must be an impartial institution to mediate between the President and the DPR, which is prone to causing arbitrariness in order to avoid abuse and regress of the constitution.